THE ANTICOAGULATION STRATEGIES FOR MANAGEMENT AND PREVENTION OF STROKE IN NEUROLOGICAL PRACTICE - Measar, Mujahed; Alyahawi, Ali (Universal Journal of Pharmaceutical Research, 2024)
Strokes are categorized as either ischemic or hemorrhagic and the specific interventions will be based on the type of stroke. About 13% of stroke is hemorrhagic and 87% is ischemic. Transient Ischemic Attacks require emergency intervention to decrease the threat of stroke, which is thought to be maximum within the first few days after TIA. Anticoagulants play a major role in the primary and secondary prevention of ischemic strokes. The optimal timing of anticoagulants initiation or resumption inpreventing and managing ischemic strokes is very important. This article will explore certain controversies surrounding this issue, while also highlighting the benefits of antithrombotic therapy used in prevention of ischemic strokes in antiphospholipid antibody syndrome (APS), atrial fibrillation, prosthetic heart valve, cancer, and vascular disorders. Aggressive local and regional efforts to organize stroke care and greater use of evidence-based recommendations may help improve outcomes. Peer Review History: Received 16 May 2024; Reviewed 11 July 2024; Accepted 24 August; Available online 15 September 2024 Academic Editor: Essam Mohamed Eissa , Beni-Suef University, Egypt, dressamceutics@yahoo.com Reviewers: Taha A.I. El Bassossy, Medicinal and Aromatic Plants Department, Desert Research Center, Cairo, Egypt, tahachemist2008@gmail.com Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com